Principles of Development - Wolpert, Lewis (New York : OUP, 2011)
The process of biological development is an amazing feat of tightly regulated cellular behaviours - differentiation, movement, and growth - powerful enough to result in the emergence of a highly complex living organism from a single cell, the fertilized egg. Principles of Development clearly illustrates the universal principles that govern this process of development, in a succinct and accessible style.Written by two highly respected and influential developmental biologists, Lewis Wolpert and Cheryll Tickle, it focuses on those systems that best illuminate the common principles covered in the text, and avoids overwhelming the reader with encyclopaedic detail.With co-authors whose expertise spans the discipline, Principles of Development combines a careful exposition of the subject with insights from some of the world's pioneering researchers in developmental biology, guiding the student from the fundamentals through to the latest discoveries in the field.
Includs Bibliographical References; Glossary 587-602p.; Index 603-616p.
Keywords: Botany; Embryology; Morphogenesis; General Science